2012
DOI: 10.1097/mcg.0b013e3182506dbb
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Rifaximin in the Primary Prophylaxis of Spontaneous Bacterial Peritonitis in Patients With Liver Cirrhosis

Abstract: Intestinal decontamination with rifaximin may prevent SBP in cirrhotic patients with ascites. Prospective randomized controlled trials are needed to confirm this finding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0
8

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(67 citation statements)
references
References 40 publications
(50 reference statements)
1
58
0
8
Order By: Relevance
“…Kalambokis et al [31] first described in cohort of 16 cirrhotic patients with no previous episode of SBP that rifaximin can reduce SIBO and BT decreasing the incidence of SBP. These results were corroborated by a retrospective study conducted by Hanouneh et al [32] in 404 cirrhotic patients in which rifaximin was used for hepatic encephalopathy and avoided the occurrence of SBP. However, two others recently published studies could not confirm these results.…”
Section: Pathophysiologysupporting
confidence: 74%
“…Kalambokis et al [31] first described in cohort of 16 cirrhotic patients with no previous episode of SBP that rifaximin can reduce SIBO and BT decreasing the incidence of SBP. These results were corroborated by a retrospective study conducted by Hanouneh et al [32] in 404 cirrhotic patients in which rifaximin was used for hepatic encephalopathy and avoided the occurrence of SBP. However, two others recently published studies could not confirm these results.…”
Section: Pathophysiologysupporting
confidence: 74%
“…A cohort study by Hanouneh et al found a transplant-free survival benefit with the use of rifaximin in cirrhotic patients with ascites and no prior history of SBP than those who didn't receive antibiotic prophylaxis. 41 Another prospective case-control study by Danulescu et al suggested that rifaximin can significantly decrease the polymorphonuclear leukocytic count in ascitic fluid of cirrhotic patients with refractory ascites compared to placebo, with a net improvement of the general condition. 42 Vlachogiannakos et al also showed that patients who received rifaximin had a significantly lower risk of developing variceal bleeding, hepatic encephalopathy (HE), SBP and hepatorenal syndrome than matched control subjects who did not receive antibiotic prophylaxis, in addition to significantly higher five-year cumulative probability of survival.…”
Section: Discussionmentioning
confidence: 98%
“…En revanche, l'utilisation de la rifaximine dans l'EH n'avait pas entrainé l'émergence de bactéries résistantes [11]. Les principales caractéristiques de la rifaximine qui pourraient expliquer ce résultat sont essentiellement liées au fait qu'elle atteint des concentrations fécales élevées en étant quasiment pas absorbée [12,13]. Du fait de la faible absorption de la rifaximine (<0,4% de passage systémique), les concentrations en antibiotique restent largement supérieures aux concentrations minimales inhibitrices des bactéries [12].…”
Section: Discussionunclassified
“…De plus, la rifaximine réduit l'expression de facteurs de virulence bactérienne et compromet le transfert de plasmides, mécanismes qui interviennent dans l'émergence de résistan-ces et n'entraine qu'une altération minime de la flore bacté-rienne intestinale. Ces caractéristiques ne sont pas propices au développement de résistances [13]. Les bactéries cocci gram positif aérobies seraient les plus susceptibles de déve-lopper ce type de résistance, selon des données in vitro.…”
Section: Discussionunclassified